Maternal exposure to alkali, alkali earth, transition and other metals: Concentrations and predictors of exposure. (September 2015) - Hinwood, A.L.; Stasinska, A.; Callan, A.C.; Heyworth, J.; Ramalingam, M.; Boyce, M.; McCafferty, P.; Odland, J.Ø.
Abstract: Most studies of metals exposure focus on the heavy metals. There are many other metals (the transition, alkali and alkaline earth metals in particular) in common use in electronics, defense industries, emitted via combustion and which are naturally present in the environment, that have received limited attention in terms of human exposure. We analysed samples of whole blood (172), urine (173) and drinking water (172) for antimony, beryllium, bismuth, cesium, gallium, rubidium, silver, strontium, thallium, thorium and vanadium using ICPMS. In general most metals concentrations were low and below the analytical limit of detection with some high concentrations observed. Few factors examined in regression models were shown to influence biological metals concentrations and explained little of the variation. Further study is required to establish the source of metals exposures at the high end of the ranges of concentrations measured and the potential for any adverse health impacts in children. Abstract : This study has demonstrated exposure to alkali, alkali earth and transition metals in pregnant women with factors such as breastfeeding, fish oil use and diet affecting exposures.